Using Virtual Reality to Assess Reading Fluency in Children - Mirault, Jonathan; Albrand, Jean-Patrice; Lassault, Julie; Grainger, Jonathan; Ziegler, Johannes C. (Frontiers in Education, 2021)
Here we provide a proof-of-concept for the use of virtual reality (VR) goggles to assess reading behavior in beginning readers. Children performed a VR version of a lexical decision task that allowed us to record eye-movements. External validity was assessed by comparing the VR measures (lexical decision RT and accuracy, gaze durations and refixation probabilities) to a gold standard reading fluency test – the one-minute reading test. We found that the VR measures correlated strongly with the classic fluency measure. We argue that VR-based techniques provide a valid and child-friendly way to study reading behavior in a school environment. Importantly, they enable not only the collection of a richer dataset than standard behavioral assessments but also the possibility to tightly control the environment.